ANALISIS PENGARUH PENEMPATAN SESUAI KEAHLIAN DAN LINGKUNGAN KERJA TERHADAP KEPUASAN KERJA GURU DI SMK NEGERI 1 BINJAI - Mutiara Salsabila Maelan; Nuzuliati Nuzuliati (CV. KAMPUS AKADEMIK PUBLISHING, 2024)
Job satisfaction in this research is an employee's attitude that describes feelings of happiness or displeasure in their work. This research aims to examine the effect of placement according to expertise and work environment on teacher job satisfaction. The population in this study were all teachers at SMK Negeri 1 Binjai, totaling 36 respondents. The data collection instrument uses a questionnaire with a Likert scale, each of which has been tested and has met the validity and reliability requirements. Data analysis used multiple linear regression using SPSS16.0forWindowssoftware tools. Theresultsofthis research showthat placement according to expertise has a positive and partially significant effect on teacher job satisfaction, the work environment has a partially positive and significant effect on teacher job satisfaction. Placement according to expertise and work environment simultaneously has a significant effect on teacher job satisfaction.